Optimization and Representativeness of Atmospheric Chemical Sampling by Hovering Unmanned Aerial Vehicles Over Tropical Forests. Issue 4 (21st April 2021) - Ma, Yongjing; Ye, Jianhuai; Ribeiro, Igor Oliveira; Vilà‐Guerau de Arellano, Jordi; Xin, Jinyuan; Zhang, Wenyu; Souza, Rodrigo Augusto Ferreira de; Martin, Scot T.
Abstract: Atmospheric chemical species play critical roles in ecosystem functioning and climate, but spatially resolving near‐surface concentrations has been challenging. In this regard, hovering unmanned aerial vehicles (UAVs) represent an emerging technology. The study herein provides guidance for optimized atmospheric sampling by hovering copter‐type UAVs. Large‐eddy simulations are conducted for species having chemical lifetimes ranging from reactive (i.e., 10 2 s) to long‐lived (i.e., 10 8 s). The case study of fair‐weather conditions over an equatorial tropical forest is used because of previous UAV deployments in this region. A framework is developed of influence length and horizontal shift of upwind surface emissions. The framework quantifies the length scale of the contribution of upwind forest emissions to species concentrations sampled by the downwind hovering UAV. Main findings include the following: (1) sampling within an altitude that is no more than 200 m above the canopy is recommended for both high‐ and intermediate‐reactivity species because of the strong decrease in species concentration even in a highly turbulent atmosphere; (2) sampling durations of at least 5 and 10 min are recommended for intermediate‐ and high‐reactivity species, respectively, because of the effects of atmospheric turbulence; and (3) in the case of heterogeneity of emissions across the underlying landscape, maximum recommended altitudes are presented for horizontal sampling strategies that can resolve the variability in the landscape emissions. The coupled effects of emission rate, wind speed, species lifetime, turbulence, and UAV sampling duration on influence length must all be considered for optimized and representative sampling over forests. Key Points: Optimized UAV sampling heights are recommended for chemical species with a variety of lifetimes UAV sampling of at least 5 min and 10 min for intermediate‐ and high‐reactivity species to minimize the influence of atmospheric turbulence Maximum sampling altitudes are recommended for horizontal sampling strategies that can resolve the variability in the landscape emissions